ASUPAN MAKANAN, STATUS GIZI DAN KETAHANAN KARDIORESPIRASI ATLET RENANG - Meirina Dwi Larasati; Serli Yuliana (Poltekkes Kemenkes Semarang, 2020)
Background: Nutrition is an important factor to achieve great performance which needs to be prepared during training by maintaining the cardio respiration health. Athletes who have balanced diet and nutritional status during training is considered to be able to increase cardio respiration health.Objectives: To determine the correlation between food intake and nutritional status on cardio respiration health of swimming athletesMethod: This research was an observational study with cross-sectional design. Fourteen swimming athletes of 10-20 years age group were selected for this study. Food intake (energy, protein, fat, and carbohydrate) were obtained by interview using 24h recall. Nutritional status were collected by measurement of BMI and body fat percentages. Cardio respiration health was assessed by measurement of VO2 max using Critical Swim Speed Test. The statistical analysis used the SpearmanTest.Results: Most subjects had an adequate energy, protein and fat intake and all subjects had an inadequate carbohydrate intake. Most of subjects had normal BMI (79%) and over body fat percentage (86%). There was correlation between food intake (energy, fat, carbohydrate) and cardio respiration health (p0.05). There was no correlation between nutritional status (BMI, body fat percentages) and cardio respiration health (p0.05).Conclusion: Adequate food intake significantly maintaining cardio respiration health of swimming athletes.